2018
DOI: 10.1186/s13068-018-1313-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing enzymatic saccharification of sugarcane bagasse by combinatorial pretreatment and Tween 80

Abstract: BackgroundThe recalcitrant structure of lignocellulosic biomass made it challenging for their bioconversion into biofuels and biochemicals. Pretreatment was required to deconstruct the intact structure by the removal of hemicellulose/lignin, improving the cellulose accessibility of enzyme. Combinatorial pretreatments with liquid hot water/H2SO4 and ethanol/NaOH of sugarcane bagasse were developed to improve enzymatic hydrolysis under mild conditions.ResultsAfter one-step 60% ethanol containing 0.5% NaOH pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…have also been reported that can decrease the non-productive adsorption of cellulase onto lignin. For example, Tween 80 and BSA could mitigate the unproductive adsorption of cellulase on lignin by binding with lignin, thus improving the access of enzymes to cellulose [ 10 , 11 ]. Lin et al [ 12 ] found that the addition of PEG could reduce the non-productive adsorption of cellulase onto lignin by forming the PEG–cellulase complex, which could disperse cellulase and avoid cellulase aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…have also been reported that can decrease the non-productive adsorption of cellulase onto lignin. For example, Tween 80 and BSA could mitigate the unproductive adsorption of cellulase on lignin by binding with lignin, thus improving the access of enzymes to cellulose [ 10 , 11 ]. Lin et al [ 12 ] found that the addition of PEG could reduce the non-productive adsorption of cellulase onto lignin by forming the PEG–cellulase complex, which could disperse cellulase and avoid cellulase aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…By delignifying the bagasse by a single step with 0.5% NaOH in ethanol, Zhang et al 47 . obtained a 17.9% removal of lignin.…”
Section: Resultsmentioning
confidence: 99%
“…By delignifying the bagasse by a single step with 0.5% NaOH in ethanol, Zhang et al 47 obtained a 17.9% removal of lignin. Lignin removal was more efficient in the alkaline and sulfite-alkaline treatments carried out by Siqueira et al, 27 with removal rates of 26.3% and 48.8%, respectively, after 60 min of reaction.…”
Section: Delignification Of Sugarcane Bagassementioning
confidence: 99%
See 1 more Smart Citation
“…In the first phase, dilute acid (i. e., 1 % w/v H 2 SO 4 ) or hydrothermal pretreatment is applied to primarily remove hemicelluloses, extractives, ash, and other non‐structural compositions from biomass . In the second phase, dilute alkali (i. e., 1 % w/v NaOH) is employed to depolymerize and dissolve lignin into the liquid stream and thereby separating it from cellulose . As shown in Table , this combinatorial pretreatment increased glucose and xylose percent yield by 9.8 % and 8.1 %, respectively, compared with the single alkali pretreatment control.…”
Section: Biomass Pretreatment and Lignin Fractionation To Modify Lignmentioning
confidence: 99%